Laser induced breakdown spectrometry for quantitative analysis of Cd in artificial sweat leachate of jewellery - Zvolská, Magdalena; Pouzar, Miloslav; Černohorský, Tomáš; Jarolím, Oldřich (University of Pardubice, 2017)
A new method has been developed for the determination of cadmium in artificial sweat leachate using laser induced breakdown spectrometry (LIBS). Small volume of liquid samples could be applied onto the solid carrier, dried under the IR lamp, and subsequently analysed by the LIBS device. For calibration, two series of standard solutions of artificial sweat were prepared: alkaline (pH 8) and acidic (pH 5.5). The known volumes of the Cd standard (with concentration of 1 ± 0.001 g l–1) were added into the samples of artificial sweat; calibration standards prepared ranging from 0-40 mg l–1 for acidic and 0-30 mg l–1 for alkaline sweat. To optimize the LIBS measurements, the regression parameters (R2, AIC, MEP) were the criteria of choice. For our purposes, three cadmium lines at wavelengths 214.44 nm, 226.50 nm, and 228.80 nm were monitored. In model solutions, the method developed has provided the limits of detection (LODs) of 0.08 mg l–1 for acidic and of 0.06 mg l–1 for alkaline sweat. The optimized method could then be used for the determination of Cd in artificial sweat leachates of jewellery samples, when the values obtained were in good agreement with the results from the reference analysis by ICP-OES. The proposed method is fast, simple, and requiring only minimal volume of samples. For analysis of leachate of jewellery, fabrics or products of daily consumption, this approach employing LIBS can be an interesting alternative to commonly used techniques, such as ICP OES or AAS.